Pro-inflammatory mediators expression by pulp cells following tooth whitening on restored enamel surface - Soares, Diana Gabriela; Sacono, Nancy Tomoko; Ribeiro, Ana Paula Dias; Leite, Maria Luisa [UNESP]; Duque, Carla Caroline de Oliveira [UNESP]; Gallinari, Marjorie De Oliveira; Pacheco, Leandro Edgar; Hebling, Josimeri [UNESP]; Costa, Carlos Alberto de Souza [UNESP] (FapUNIFESP (SciELO), 2022)
This paper aimed to assess the influence of adhesive restoration interface on the diffusion of hydrogen peroxide (H2O2), indirect toxicity, and pro- inflammatory mediators expression by odontoblast-like cells, after in-office tooth whitening. Dental cavities prepared in bovine enamel/dentin discs were adhesively restored and subjected or not to hydrolytic degradation (HD). A whitening gel with 35% ^CMWG) was applied for 45 min onto restored and non-restored specimens adapted to artificial pulp chambers giving rise to the groups: SD- intact discs (control); SD/HP- whitened intact discs; RT/HP- restored and whitened discs; and RT/HD/HP- restored and whitened discs subjected to HD. The extracts (culture medium + WG components diffused through enamel/dentin/restoration interface) were collected and applied to odontoblast-like MDPC-23 cells. The study evaluated the amount of H2O2 in the extracts, as well as the cell viability (CV), cell morphology (CM), and gene expression of inflammatory mediators (TNF-a and COX-2) by the pulp cells exposed to the extracts (ANOVA and Tukey tests; 5% significance). All whitened groups presented lower CV than SD (control; p<0.05). The highest CV reduction and gene expression of TNF-a and COX-2 was observed in the RT/HD/HP group in comparison with SD/HP and RT/HP (control; p<0.05). CM alterations occurred in all whitened groups. The intensity of these cell side effects was directly related with the amount of H2O2 in the extracts. We concluded that adhesive restoration of dental cavity increases the H2O2 diffusion after in-office whitening, enhancing the indirect toxicity of this therapy and trigger pro-inflammatory overexpression by MDPC-23 cells.
Keywords: Adhesion; Inflammation; Odontoblasts; Tooth-bleaching; Toxicity